PENERAPAN KESELAMATAN DAN KESEHATAN KERJA PADA LABORATORIUM KONSTRUKSI SIPIL JURUSAN TEKNIK SIPIL – POLITEKNIK NEGERI MANADO - Pangemanan, Syanne; Rangkang, Jeanely (Universitas PGRI Yogyakarta, 2019)
Civil Construction laboratories are the means to conduct student work practices. Civil Construction Laboratory with all equipment and materials is a place of potential cause danger to the users of lecturers, technicians and students in it if not equipped with knowledge about health and Occupational safety. The cost to build occupational safety and health, the cost to buy security tools is quite large. However, occupational safety and health will also be assured. Workers ' skills and skills must be increased through education and training so as to follow the pace of development of science and technology disaster relief tools should be improved to make the catastrophe caused by the implementation of Advanced technology is not until widespread and destructive. But currently the use of safety equipment for the implementation of practice in the Civil Construction Laboratory of Civil Engineering Department of Manado State Polytechnic is still lacking. The specific purpose of dissemination of technological products to the communities to be achieved is (1) protecting and guaranteeing the safety of any lecturers, technicians, students and other people in the workplace; (2) Training K3 for lecturers and Technicians (3) The K3 Handbook for Civil Construction Laboratories. To achieve these objectives, then through the targeted external indicators are: (1) K3 equipment is personal protective equipment (APD) in the form of helmets, masks, vests, gloves and safety shoes (2) K3 Handbook, (3) Training services of K3 for lecturers and technicians and (4) publications on Local on-line mass media.